2017
DOI: 10.1038/s41598-017-05838-4
|View full text |Cite
|
Sign up to set email alerts
|

Assuring quality in microplastic monitoring: About the value of clean-air devices as essentials for verified data

Abstract: Avoiding aerial microfibre contamination of environmental samples is essential for reliable analyses when it comes to the detection of ubiquitous microplastics. Almost all laboratories have contamination problems which are largely unavoidable without investments in clean-air devices. Therefore, our study supplies an approach to assess background microfibre contamination of samples in the laboratory under particle-free air conditions. We tested aerial contamination of samples indoor, in a mobile laboratory, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(118 citation statements)
references
References 25 publications
5
111
1
1
Order By: Relevance
“…For future studies we strongly recommend a more thorough cleaning of plastic particles with filtered, ultrapure water. Furthermore, it is interesting to note that despite taking a forensic approach during the extraction of microplastics (Wesch et al, 2017) we noted a large amount of fibres (98%) amongst the sampled microplastics. This is in agreement with other findings (Lusher et al, 2013(Lusher et al, , 2016Neves et al, 2015;Rochman et al, 2015;Bellas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For future studies we strongly recommend a more thorough cleaning of plastic particles with filtered, ultrapure water. Furthermore, it is interesting to note that despite taking a forensic approach during the extraction of microplastics (Wesch et al, 2017) we noted a large amount of fibres (98%) amongst the sampled microplastics. This is in agreement with other findings (Lusher et al, 2013(Lusher et al, , 2016Neves et al, 2015;Rochman et al, 2015;Bellas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The extraction of microplastics and subsequent examination of the filters was performed in compliance with the most recent findings in microplastic contamination prevention methodologies (Woodall et al, 2015;Wesch et al, 2017). All equipment used was pre-rinsed with 0.2 µm filtered MilliQ TM water and all clothing worn during laboratory work was of nonpolymer nature.…”
Section: Contamination Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discounting the low number found in pre-twentieth-century mud and likely occurrence from modern contamination (Woodall et al 2015;Wesch et al 2017;Willis et al 2017), it may be significant that the few coloured fibres found were red. Fibres of the same colour and form were identified in the upper 50 cm of the core as possibly being made of polysulphide rubber (Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…This proportion of identified versus unidentified particles is common in aquatic microplastic studies using Raman spectroscopy (identified 41-67%) (Ballent et al 2016;Clunies-Ross et al 2016;Frère et al 2017). Because of the low number and size of microplastics found, and the ubiquity of microfibres found in urban atmospheres, contamination during coring and processing (Woodall et al 2015;Wesch et al 2017) must be acknowledged as a possible source of error. The number of fibres in the blanks examined during processing, and their potential influence on the interpretation of early plastic occurrence, is recognized.…”
Section: Methodological Limitationsmentioning
confidence: 98%